Making Democracy Work for the Poor in India: a Governance Challenge. - Rizvi, Gowher (2007)
There has emerged in many societies a broad consensus that orderly and effective governance requires a multi-sector approach in which government, civil society and the market perform specific roles sometimes independently, sometimes in support of each other and at times even in opposition to each other. While these new governance arrangements have contributed to efficiency and effectiveness, they appear to have sacrificed equity and social justice. They have contributed to a hollowing of the public values that ensure the very foundations of social and economic justice and often do not provide safeguards that prevent cronyism and corruption. In the context of such a wide-scale organisational change, this paper explores the case of India’s democracy and its continuing struggles with unequal economic growth and social marginalisation. It argues that democratic governance and institutions have served India well but in order to tackle the problem of poverty and equity, the democratic institutions will have to be strengthened and citizens put at the core of the governance concern.